La permanencia de la lengua quechua en Huaycán - Sara Lafosse, Mercedes Giesecke (2008)
The present article treats on the survey done in six educative institutions in the locality of Huaycan, on the knowledge and use of Quechua within a scholastic population of these six educative institutions in Huaycan in the district of Ate- Vitarte in the department of Lima. This study is framed in the development of the field work of the investigation on «Multiculturalism and education in Peru» that I come making for my studies from the doctorate in social sciences in the UNMSM. In this occasion I will display the data collected by the work of field.